The Wiley 5G REF Security - Tafazolli, Rahim (John Wiley & Sons, Incorporated, 2021)
Cover -- Title Page -- Copyright -- Contents -- Foreword -- List of Contributors -- Chapter 1 5G Mobile Networks Security Landscape and Major Risks -- Introduction -- 4G to 5G: A Paradigm Shift -- 5G System Architecture -- Salient Features of 5G Network -- The Threat Landscape and Security Roadmap -- 5G Network Threat Surface -- Inspecting 3GPP Security Proposals -- Security Research Groups and Visions -- Why Securing 5G is Challenging? -- Billions of Hackable IoT Devices -- The Convergence of IT and Telecom Infrastructure -- Open‐source Softwarization -- AI vs AI -- Real‐time E2E Security Monitoring at Scale -- Physical Layer Security -- Can 3GPP Recommendations Solely Secure the 5GS? -- Current State of the Arts and Open Research Areas -- Conclusion -- Acronyms -- Related Articles -- References -- Further Reading -- Chapter 2 SDMN Security -- Software‐defined Mobile Network (SDMN) Security -- Introduction -- SDN Concepts -- SDN Vulnerabilities -- SDN Security -- Security Function Implementations -- Advanced Detection Algorithms -- Data Plane Extensions -- Security Monitoring and Policy Enforcement -- Conclusion and Future Trends -- Related Articles -- References -- Further Reading -- Chapter 3 5G Security - Complex Challenges -- Introduction 5G Security Building Blocks -- Old Challenges in New Context for 5G -- New Security Research Challenges for 5G -- Trust -- Dimension 1: Trust Stack -- Dimension 2: E2E Trust -- Dimension 3: Supply Chain Integrity -- Dimension 4: Dynamicity -- Malware in Mobile Core Networks -- Measuring Security -- Need for a Comprehensive and Regular Risk Management Approach -- Status Regulatory Approaches for Risk Management -- How to Proceed Today in 5G Risk Management Approach -- Latest Proposal for 5G Risk Management -- Summary -- Related Articles -- References -- Further Reading
Description based on publisher supplied metadata and other sources
Keywords: Mobilfunk; 5G